The art of art for children's books : a contemporary survey - Klemin, Diana (New York : Clarkson N. Potter, 1966)
Examples of the work of sixty-seven established illustrators of contemporary children's books. Includes very brief details on style, technique. and medium.
Bibliography: p. 125.
Keywords: Illustrated books, Children's -- History and criticism; Illustrators